Correction: Effects of small-sided games vs. simulated match training on physical performance of youth female handball players. - Rasa Mikalonytė; Rūtenis Paulauskas; Eduardo Abade; Bruno Figueira (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0273574.].